2014
DOI: 10.1073/pnas.1316376111
|View full text |Cite
|
Sign up to set email alerts
|

VipD is a Rab5-activated phospholipase A 1 that protects Legionella pneumophila from endosomal fusion

Abstract: A crucial step in the elimination of invading microbes by macrophages is phagosomal maturation through heterotypic endosomal fusion. This process is controlled by the guanine nucleotide binding protein Rab5, which assembles protein microdomains that include the tethering protein early endosomal antigen (EEA) 1 and the phosphatidylinositol (PI) 3-kinase hVps34, which generates PI(3)P, a phospholipid required for membrane association of EEA1 and other fusion factors. During infection of macrophages, the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
146
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 23 publications
1
146
0
Order By: Relevance
“…To identify more clearly whether the ACT-PLA activity cleaves specifically the sn-1 or the sn-2 ester bond of the lipid substrate, we used highly sensitive fluorogenic phospholipid substrates called PED-A1 [N-((6-(2,4-DNP)Amino)Hexanoyl)-1-(BODIPY FL C5)-2-Hexyl-Sn-Glycero-3-Phosphoethanolamine] (which measures PLA 1 activity) and PED6 [N-((6-(2,4-Dinitrophenyl)amino)hexanoyl)-2-(4,4-Difluoro-5,7-Dimethyl-4-Bora-3a,4a-Diaza-s-Indacene-3-Pentanoyl)-1-Hexadecanoyl-snGlycero-3-Phosphoethanolamine] (which measures PLA 2 activity) (34). Both substrates are modified glycerophosphoethanolamines with BODIPY FL dye-labeled sn-1 or sn-2 acyl chains, respectively, and a dinitrophenyl group conjugated to the polar head group of the lipid to provide intramolecular quenching.…”
Section: Resultsmentioning
confidence: 99%
“…To identify more clearly whether the ACT-PLA activity cleaves specifically the sn-1 or the sn-2 ester bond of the lipid substrate, we used highly sensitive fluorogenic phospholipid substrates called PED-A1 [N-((6-(2,4-DNP)Amino)Hexanoyl)-1-(BODIPY FL C5)-2-Hexyl-Sn-Glycero-3-Phosphoethanolamine] (which measures PLA 1 activity) and PED6 [N-((6-(2,4-Dinitrophenyl)amino)hexanoyl)-2-(4,4-Difluoro-5,7-Dimethyl-4-Bora-3a,4a-Diaza-s-Indacene-3-Pentanoyl)-1-Hexadecanoyl-snGlycero-3-Phosphoethanolamine] (which measures PLA 2 activity) (34). Both substrates are modified glycerophosphoethanolamines with BODIPY FL dye-labeled sn-1 or sn-2 acyl chains, respectively, and a dinitrophenyl group conjugated to the polar head group of the lipid to provide intramolecular quenching.…”
Section: Resultsmentioning
confidence: 99%
“…VipD is a T4SS-translocated substrate of Legionella pneumophila, the causative agent of a potentially fatal pneumonia known as Legionnaires' disease, and another example of an effector whose catalytic activity depends on the presence of a host factor (11)(12)(13)(14). Following uptake by human alveolar macrophages, L. pneumophila translocates VipD together with more than 250 other effector proteins through its Dot/Icm T4SS into the host cell cytoplasm (15).…”
mentioning
confidence: 99%
“…Although the precise biological role of most L. pneumophila effectors remains unclear, we recently showed that VipD is important for endosomal avoidance by LCVs. The protein localizes to endosomes presumably by binding to the small GTPases Rab5 or Rab22, key regulators of endosomal function (13,14). Rab GTPase binding to the C-terminal domain of VipD triggers robust phospholipase A1 (PLA 1 ) activity within the Nterminal domain, resulting in the removal of phosphatidylinositol 3-phosphate [PI(3)P] and potentially other lipids from endosomal membranes (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations